Comparing role of laparoscopy, ultrasound and clinical examination in pelvic pain - Bharwani, Hema; Jain, Meena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pelvic pain is a frequent and poorly understood complaint in women of reproductive age group, which is one of the most perplexing problems faced by the gynaecologist. This study was conducted to detect the cause of pelvic pain and to correlate clinical diagnosis, ultrasound, and laparoscopic di-agnosis and formulate treatment modalities. Methods: This study was conducted in the Department of Obstetrics and Gynecology, JLN Hospital and RC, Bhilai, Chattisgarh during the one year period from September 2014 to August 2015. 97 women belonging age 15 to 65 years with history of pelvic pain (acute / chronic) were admitted after excluding history of acute abdominal trauma, diagnosed gynaecological malignant disorder, severe cardiac/respiratory disease or signs of peritonitis. A detailed history was taken and clinical examination was done. Results: The age group in the present study was between 15 to 65 years. Among them, 36% cases belonged to 20-30 years age group. Clinically the most common sign was abdominal tenderness (59.89%). Clinically 47 cases (48.45%) had abnormal findings, on ultrasonography 61 cases (62.88%) had abnormal findings as compared to laparoscopy which could detect 75 cases (77.32%) showing abnormality. Most common pelvic pathology was adhesions (17.52%) followed by PID (14.43%). None of the cases of adhesions, fimbrial cyst, pelvic congestion syndrome and appendicitis were diagnosed clinically or ultrasonographically, all cases were diagnosed on laparoscopy. The sensitivity and specificity of clinical examination is 54% and 49% as compared to laparoscopy respectively. The PPV and NPV of clinical examination is 24% and 78% respectively. The sensitivity and specificity of ultrasonography is 59% and 69% as compared to laparoscopy respectively. The PPV and NPV of Ultrasonography is 36% and 85% respectively. Appropriate surgical intervention like salphingooopherectomy, adhesiolysis, myomectomy, hysterectomy was carried out laparoscopically. Conclusions: Laparoscopy eliminates the diagnostic error and corrects the wrong diagnosis. Laparoscopy is a more sensitive and superior method for evaluation of pelvic pain as compared to Ultrasonography. Laparoscope has definitive place in evaluating patients with pelvic pain and often a definitive procedure can be undertaken with the laparoscope without subjecting the patient to laparotomy.